Parenthood Wage Differentials in South Korea - Choi, Seulki; Mingean Park (KDI School of Public Policy and Management, 2019)
Is there wage differential by parenthood? If then, how is it different by gender and cohort? This study is to study motherhood penalty and fatherhood premium in South Korea using the Korean Labor and Income Panel Study (KLIPS) data. In the essence of the study overall, men have gained the fatherhood premium, while women do not. In addition, the fatherhood premium is getting weaker, but the motherhood penalty is getting stronger in Korean case. It shows that young generation including young men are suffering from wage penalty due to parenthood.
Keywords: Fatherhood Premium; Motherhood Penalty; Parenthood Wage Differential; Generation